1993
DOI: 10.1128/jb.175.6.1561-1571.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of paralogous and orthologous members of the superoxide dismutase gene family from genera of the halophilic archaebacteria

Abstract: Four species representing three genera of halophilic archaebacteria were examined for the presence of genomic sequences that encode proteins of the superoxide dismutase family. Three species, Halobaterium cutirubrum, Halobacterium sp. strain GRB, and Haloferax volcanii, contain duplicated (paralogous) genes of the sod family; a fourth species, Haloarcula marismortui, contains only a single gene. These seven genes were cloned and sequenced, and their transcripts were characterized by Northern (RNA) hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The consensus derived from these phylogenetic analyses is illustrated in Fig. 4 (7,25). This finding suggests that the halophilic ancestor may also have had only a single sod gene in its genome.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The consensus derived from these phylogenetic analyses is illustrated in Fig. 4 (7,25). This finding suggests that the halophilic ancestor may also have had only a single sod gene in its genome.…”
Section: Resultsmentioning
confidence: 90%
“…SOD activity has been detected in at least two representatives of the ancestral methanogen group and in numerous halophilic species (7,10,25). The SOD enzyme from both Halobacterium cutirubrum and its immediate relative, H. halobium, has been purified and extensively characterized; the enzyme contains Mn as a metal ion cofactor and is related to the Mnor Fe-type enzymes of eubacteria (13,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of these 22 probes gave multiple signals in both genomes. We do not know the nature of the repeated sequences; they may represent gene families as have been documented for the haloarchaea (1,17,21,23,41), insertion sequences (especially in the plasmids [7] though of uncharacterized types [14]), or other repeat sequence structures (34).…”
Section: Hybridization Of Probes To Dot and Southern Blotsmentioning
confidence: 99%
“…The third difference is that Tyr-77 in FeSODs is changed to phenylalanine in Mn-SODs [9][10][11][12][13]. Although a few exceptions have been reported [17,18], these three differences could be the primary candidates to account for the metal specificity of the Fe-and Mn-SOD activity [19], improving on the suggestions by Parker and Blake [20] and Yamakura et al [21]. Recently, Yamano and Maruyama [22] reported that the substitution of Tyr-77 by Phe in the metal-specific Fe-SOD from Sulfolobus solfataricus did not change the metal-specific activity of the enzyme.…”
Section: Introductionmentioning
confidence: 99%